2003
DOI: 10.1182/blood-2003-02-0517
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12 expression by invasive trophoblasts induces the specific migration of CD16– human natural killer cells

Abstract: In the maternal decidua, natural killer (NK) cells, characterized by lack of CD16, are found in direct contact with the fetal extravillous trophoblasts (EVTs). It is yet unknown which factors contribute to the specific homing of this unique NK subset to the decidua. In this study we analyze the chemokine receptor repertoire on various NK populations derived from the peripheral blood and decidua. We show that CXCR4 and CXCR3 receptors are preferentially expressed on CD16 ؊ NK subsets derived either from the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
266
1
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 314 publications
(292 citation statements)
references
References 52 publications
17
266
1
5
Order By: Relevance
“…In correlation with these observations, CD56 bright CD16 Ϫ cells have been shown as important players in regulating and priming immune responses via cytokine-mediated cross-talk with neighboring dendritic (DC) and T cells (6,10). In contrast, the more cytotoxic subset, CD56 dim CD16 ϩ , has higher levels of CXCR1 and CX3CR1 chemokine receptors (7,8), and therefore is preferentially recruited to sites of inflammation (4). Signals transduced by locally secreted inflammatory cytokines and specific encounters with target cells synergize to induce activation of this subset.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…In correlation with these observations, CD56 bright CD16 Ϫ cells have been shown as important players in regulating and priming immune responses via cytokine-mediated cross-talk with neighboring dendritic (DC) and T cells (6,10). In contrast, the more cytotoxic subset, CD56 dim CD16 ϩ , has higher levels of CXCR1 and CX3CR1 chemokine receptors (7,8), and therefore is preferentially recruited to sites of inflammation (4). Signals transduced by locally secreted inflammatory cytokines and specific encounters with target cells synergize to induce activation of this subset.…”
mentioning
confidence: 69%
“…7). One explanation for the activated-like phenotype of the decidual NK subset can be inferred from the chronic intimate interaction of these cells with semiallogeneic extravillous trophoblasts that invade maternal decidua and the cytokine-enriched local microenvironment (7,64). Such conditions might induce, at least, a partial activation state on NK cells found in the decidua.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CXCR4 has been previously implicated in migration and activation of MDSCs in cancer (40,41). CXCL12, the ligand for CXCR4, has been shown to be expressed by trophoblast and decidual stromal cells and to be responsible for homing of decidual NK cells (42,43). Recently, Zhao et al (37) showed an association of an upregulation of CXCL12 and an accumulation of MDSCs in the pregnant mouse uterus.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect evidence suggests that CD56 bright CD16 2 dNK cells originate from CD56 bright CD16 2 pNK cells. 37,38 In this study, our results showed that trophoblasts had no effect on the expression of cell surface molecules or intracellular cytokines by CD56 bright pNK cells, also suggested the resemblance of peripheral CD56 bright NK cells to dNK cells (Supplementary Figure 2). Our previous studies demonstrated that at the maternal/fetal interface, CXCL12 was mainly produced by trophoblasts and to a lesser extent by decidual stromal cells, while CXCR4 was intermediately expressed on dNK cells and highly expressed on peripheral NK cells (Ref.…”
Section: Discussionmentioning
confidence: 69%